2011
DOI: 10.1038/ng.812
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a common variant associated with risk of endometrial cancer

Abstract: Endometrial cancer is the most common malignancy of the female genital tract in developed countries. To identify genetic variants associated with endometrial cancer risk, we undertook a genome-wide association study involving 1,265 endometrial cancer cases from Australia and the UK and 5,190 controls from the Wellcome Trust Case Control Consortium. Genotype frequencies in cases and controls were compared for 519,655 SNPs. Forty-seven SNPs that showed evidence of association with endometrial cancer in stage 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 39 publications
6
155
0
1
Order By: Relevance
“…It remains possible that HNF1B may cooperate with ERBB2 to drive transformation in a manner analogous to what has been observed for YAP1 and CIAP1, which reside in a single amplicon in hepatocellular cancer (Zender et al 2006). HNF1B has previously been described as an essential gene in ovarian clear cell carcinoma, where it is highly expressed (Tsuchiya et al 2003), and genome-wide association studies have associated SNPs in the HNF1B locus with risk for prostate and endometrial cancers (Schumacher et al 2011;Spurdle et al 2011), although HNF1B may also be epigenetically inactivated in certain contexts (Terasawa et al 2006). Developmentally, HNF1B is required for visceral endoderm formation (Barbacci et al 1999) and proper development of the genitourinary tract (Ryffel 2001;Bellanne-Chantelot et al 2005), but appears to be dispensable in adult tissue (Verdeguer et al 2009), making it a reasonable candidate for therapeutic targeting.…”
Section: Discussionmentioning
confidence: 85%
“…It remains possible that HNF1B may cooperate with ERBB2 to drive transformation in a manner analogous to what has been observed for YAP1 and CIAP1, which reside in a single amplicon in hepatocellular cancer (Zender et al 2006). HNF1B has previously been described as an essential gene in ovarian clear cell carcinoma, where it is highly expressed (Tsuchiya et al 2003), and genome-wide association studies have associated SNPs in the HNF1B locus with risk for prostate and endometrial cancers (Schumacher et al 2011;Spurdle et al 2011), although HNF1B may also be epigenetically inactivated in certain contexts (Terasawa et al 2006). Developmentally, HNF1B is required for visceral endoderm formation (Barbacci et al 1999) and proper development of the genitourinary tract (Ryffel 2001;Bellanne-Chantelot et al 2005), but appears to be dispensable in adult tissue (Verdeguer et al 2009), making it a reasonable candidate for therapeutic targeting.…”
Section: Discussionmentioning
confidence: 85%
“…Mutations of HNF1B have been described in renal cell carcinoma (33), and epigenetic silencing of the gene has been reported in ovarian cancer, as well as gastric, pancreatic, and colorectal cell lines (34). GWAS have implicated variants in the HNF1B locus in diabetes and endometrial cancer risk (35,36). SLC22A3 is a member of the solute carrier family 22; it functions as a cation transporter in various organs, including prostate tissue, and plays a role eliminating small organic cations and toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the two SNPs (rs4430796 and rs11649743) in HNF1B associated with prostate cancer risk were identified (20,21). Further study indicated that the rs4430796 is also associated with endometrial cancer risk in women of European background (22). Similarly, rs7501939 in HNF1B is associated with the risk of prostate cancer (22) and endometrial cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…Further study indicated that the rs4430796 is also associated with endometrial cancer risk in women of European background (22). Similarly, rs7501939 in HNF1B is associated with the risk of prostate cancer (22) and endometrial cancer (22). In ovarian cancer, HNF1B is identified as a subtype-specific susceptibility gene (24-26).…”
Section: Introductionmentioning
confidence: 99%